The Strength of Lower Limbs in Elite Gymnasts and Swimmers - Aleksander Wiażewicz; Waldemar Wiśniowski; Tomasz Sacewicz; Magdalena Czajka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
Critical moments during gymnastic exercises are those related to landing and suppressing overloads, transmitted through lower limbs. A swimmer's lower limbs provide a good body position in the water and maintain the balance. Both in sports authors postulate reaching bilateral, steady development of the athlete's body. The main aim was identification and a comparative analysis of the hip, knee and ankle joints flexors and extensors strength, of highly qualified gymnasts and swimmers. Ten healthy subjects participated in the investigation. Five gymnasts (22.2 ±7.3 y.o., 169.4 ±3.91 cm, 64.4 ±3.78 kg) and five swimmers (20.5 ±1.3 y.o., 186.2 ±1.64 cm, 78.4 ±2.61 kg) were highly qualified Polish athletes. Strength measurements were made on Biodex S4 isokinetic dynamometer. Subjects performed hip extension/flexion in lying position, knee extension/flexion and ankle plantar/dorsi flexion. Strength parameters of the lower limbs differentiate gymnasts and swimmers. Lower limb's strength parameters can be used during training, control, selection or prevention. To achieve a high sport level, swimmers must demonstrate higher strength parameters of lower limbs than gymnasts. The value of work in the maximum repetition (MRW) should be thoroughly analyzed. Highly qualified gymnasts and swimmers should take into account the harmonious, bilateral strength development of the lower limbs.